DEVELOPMENT OF PROBLEM LEARNING TECHNOLOGY AS A MEANS OF SELF-DEVELOPMENT OF PERSONALITY IN THE EDUCATIONAL PROCESS - Topuzov О.М. (Pedagogy of Higher and Secondary Education, 2022)
The article is devoted to disclosure of methodological foundations of the realization technology of problem-based gaming Completed a comparative analysis of techniques and technologies to the technology problem-based gaming, which ensures the implementation of procp Es of person-centered education.